Use of dexamethasone in idiopathic, acute pediatric rhabdomyolysis. Issue 2 (10th December 2020) - Summerlin, Maxwell L.; Regier, Debra S.; Fraser, Jamie L.; Chapman, Kimberly A.; Kafashzadeh, Dariush; Billington, Charles; Kisling, Monisha; Grochowsky, Angela; Ah Mew, Nicholas; Shur, Natasha
Abstract: Current rhabdomyolysis treatment guidelines vary based on the etiology and diagnosis, yet many cases evade conclusive diagnosis. In these cases, treatment options remain largely limited to fluids and supportive therapy. We present two cases of acute rhabdomyolysis diagnosed in the emergency department: a 5‐year‐old boy with sudden onset bilateral flank pain, and a 13‐year‐old boy with 2–3 days of worsening pectoral and shoulder pain. Each patient had a prior similar episode requiring hospitalization in the past. The 5‐year‐old had no inciting trauma or trigger, medication use, or illness. The 13‐year‐old previously had an upper respiratory infection during the week prior and had been strenuously exercising at the time of onset. Genetic testing results were unknown for both patients during their hospitalizations, and insurance and other barriers led to delay. Later results for the first patient revealed a heterozygous deletion in intron 19 on the LPIN1 gene interpreted as a variant of unknown significance. During their hospitalizations, both children were started on intravenous ( i . v .) fluids, and creatine kinase (CK) initially trended downward, but then began to rise or plateau. After reviewing the cases, prior literature, and anecdotal evidence of benefit from corticosteroid therapy in rhabdomyolysis with our consultant metabolic physicians, dexamethasone was initiated. In both patients, dexamethasone use correlated with relief of patient symptoms, significantly decreased CK value, and our ability to discharge these patients home quickly. Our cases, discussion, and literature review all lead to the consideration of the use of dexamethasone in conjunction with standard therapy for acute rhabdomyolysis.